IMPLEMENTASI SOCIAL MEDIA OPTIMIZATION (SMO) SEBAGAI INTERNET MARKETING PADA FACEBOOK RUMAHDAN PROPERTI.COM - Saragih, Hoga; Chandra, David (Teknik dan Ilmu Komputer, 2012)
Rumahdanproperti.com is the largest property advertising portal website in Indonesia which focuses its business by online. Rumahdanproperti.com have used the method of Search Engine Optimization (SEO) which is more focused on the optimization of keywords on search engines in introducing the products offered. This research will implement the SMO method using facebook as a means of product introductions and analyze the use of existing features in response to facebook support rumahdanproperti.com ads. The results of the implementation of the SMO is expected to become one of the IT strategies that can be used by the company to improve the response ad on the website rumahdanproperti.com.ÃÂ ÃÂ Keywords: social media optimization, SMO facebook, implementasi SMO